Best in Show Winners. Issue 5 (1st September 2018) - Donelan, Jenny
Abstract : The Society for Information Display honored four exhibiting companies with Best in Show awards at Display Week 2018 in Los Angeles: Ares Materials, AU Optronics, Tianma, and Visionox.